Uplink SDMA with Limited Feedback: Throughput Scaling. (29th January 2008) - Huang Huang, Kaibin Kaibin; Heath Heath, Robert W. Robert W.; Andrews Andrews, Jeffrey G. Jeffrey G.
Abstract : Combined space division multiple access (SDMA) and scheduling exploit both spatial multiplexing and multiuser diversity, increasing throughput significantly. Both SDMA and scheduling require feedback of multiuser channel sate information (CSI). This paper focuses on uplink SDMA with limited feedback, which refers to efficient techniques for CSI quantization and feedback. To quantify the throughput of uplink SDMA and derive design guidelines, the throughput scaling with system parameters is analyzed. The specific parameters considered include the numbers of users, antennas, and feedback bits. Furthermore, different SNR regimes and beamforming methods are considered. The derived throughput scaling laws are observed to change for different SNR regimes. For instance, the throughput scales logarithmically with the number of users in the high SNR regime but double logarithmically in the low SNR regime. The analysis of throughput scaling suggests guidelines for scheduling in uplink SDMA. For example, to maximize throughput scaling, scheduling should use the criterion of minimum quantization errors for the high SNR regime and maximum channel power for the low SNR regime.